Elected in a close race: Mayor's characteristics and local public finances - Fabiana Rocha; Veronica Ines Fernandez Orellano; Karina Bugarin (EconomiA, 2018)
The purpose of this paper is to evaluate the role of mayor's characteristics (education, experience and gender) on fiscal indicators of Brazilian municipalities. We use regression discontinuity and the outcomes of close elections to identify causal effects for 2000, 2004 and 2008. We find evidence that experienced and educated mayors choose to devote a smaller fraction of the budget to current and personnel expenditures, and so they seem to be concerned with the quality of public finances. Moreover, educated mayors are better in negotiating discretionary transfers. Unfortunately, the results indicate that women and men elected in close races are different regarding education, and therefore we were not able to evaluate the effect of gender on fiscal indicators.
Keywords: C31; H41; H83; 330; Education; Experience; Fiscal indicators; Mayors; Regression discontinuity design